International fraud handbook - Wells, Joseph T. (Wiley, 2018)
Introduction -- Legal issues pertaining to fraud -- Fraud risk assessment -- Preventing and detecting fraud -- Fraud investigation -- Interviewing witnesses and suspects -- Asia-Pacific region -- Canada -- Eastern Europe and Western/Central Asia -- Latin America and the Caribbean -- Middle East and North Africa -- Southern Asia -- Sub-Saharan Africa -- United States -- Western Europe